Análise ergonômica de instrumentos líticos pré-históricos brasileiros: uma contribuição para a história da ergonomia - Menin, Mariana [UNESP] (2014)
Ergonomics is a science, if not the only one, with the exact date of its appearance - July 12, 1949. In Brazil, this science is just a little more than 30 years of age. The history of Ergonomics - i.e. the entire period following its date of birth - has been extensively studied in Brazil and worldwide. But what precedes this history, which we may call the pre-history of Ergonomics, has been little debated until now. For many authors, the beginning of this relates to the creation of the first Man-made tools, i.e. when primitive man feels the need to adapt tools to facilitate their everyday tasks. Thus, Archeology - the science that studies Man's past through material remains of their activities, can be an important tool for invesetigating this hypothesis and to understand the criteria that man already sought like comfort, safety and ease of construction of their tools. The aim of this thesis is the analysis of chipped stone tools developed by prehistoric men, specially, evaluating the grips/handles of their tools, being possible to provide data and information to contextualize the history of Ergonomics in Brazil. Lithic artifacts from the CEMAARQ of the UNESP of Presidente Prudente (SP), from the Museum the Archaeology and Paleontology of Araraquara (SP) and from the Municipal Museum of Jahu (SP) were used as objects os study. The archaeological pieces chosen were molded using a mixture of polyurethane liquid rubber (silicone mold). With the aid of the molds, the archaeological tools were reproduced accurately - regarding weight and color - in polyester resin and an addition of sand and micro spheres of iron. After the reproduction of the pieces, the grips/handles were analyzed. The method used for assessing the type of grip was the use of gloves equipped with FSRs sensors, which record the loads during the simulation of possible activities performed with lithic tools